Salt-Tolerant Plant Growth Promoting Rhizobacteria for Enhancing Crop Productivity of Saline Soils - Egamberdieva, Dilfuza; Wirth, Stephan; Bellingrath-Kimura, Sonoko Dorothea; Mishra, Jitendra; Arora, Naveen K. (Frontiers in Microbiology, 2019)
Soil salinity has emerged as a serious issue for global food security. It is estimated that currently about 62 million hectares or 20 percent of the world’s irrigated land is affected by salinity. The deposition of an excess amount of soluble salt in cultivable land directly affects crop yields. The uptake of the high amount of salt inhibits diverse physiological and metabolic processes of plants even impacting their survival. The conventional methods of reclamation of saline soil which involve scraping, flushing, leaching or adding an amendment (e.g. gypsum, CaCl2, etc.) are of limited success and also adversely affect the agro-ecosystems. In this context, developing sustainable methods which increase the productivity of saline soil without harming the environment are necessary. Since long, breeding of salt-tolerant plants and development of salt-resistant crop varieties have also been tried, but these and aforesaid conventional approaches are not able to solve the problem. Salt tolerance and dependence are the characteristics of some microbes. Salt-tolerant microbes can survive in osmotic and ionic stress. Various genera of salt-tolerant plant growth promoting rhizobacteria (PGPR) have been isolated from extreme alkaline, saline, and sodic soils. Many of them are also known to mitigate various biotic and abiotic stresses in plants. In the last few years, their potential in enhancing the productivity of crop plants facing salt-stress has been researched upon clearly suggesting that the salt tolerant PGPR (ST-PGPR) can be exploited in the reclamation of saline agroecosystems. In this review, ST-PGPR and their potential in enhancing the productivity of saline agroecosystem will be discussed. Apart from this, PGPR mediated mechanisms of salt tolerance in different crop plants and future research trends of using ST-PGPR for reclamation of saline soils will also be highlighted.